2013
DOI: 10.1080/20445911.2012.739153
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in personality and face identification

Abstract: Word count (excluding abstract, figure legends and references): 3052 2 ! AbstractUnfamiliar face identification is characterized by substantial variation between individual observers, but the cause of this variation is largely unknown. This study investigated whether individual differences in face identification are linked to an observerÕs personality, by combining performance on an established face-matching test with two in-depth personality assessments (the 16PF5 and the NEO-PI-R). The face test revealed a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
59
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 40 publications
(53 reference statements)
2
59
3
Order By: Relevance
“…However it may be that our measure of personality (TIPI) is not detailed enough to provide a good measure of anxiety, which is a facet of neuroticism (synonymous with emotional stability in the TIPI scale). Furthermore, this correlation was only found for female participants (Megreya & Bindemann, 2013). Later analysis of our results, found a significant difference between males and females in terms of emotional stability, t(98) = 2.21, p = .03, but neither group correlated with matching ability.…”
Section: Discussioncontrasting
confidence: 61%
“…However it may be that our measure of personality (TIPI) is not detailed enough to provide a good measure of anxiety, which is a facet of neuroticism (synonymous with emotional stability in the TIPI scale). Furthermore, this correlation was only found for female participants (Megreya & Bindemann, 2013). Later analysis of our results, found a significant difference between males and females in terms of emotional stability, t(98) = 2.21, p = .03, but neither group correlated with matching ability.…”
Section: Discussioncontrasting
confidence: 61%
“…More recent results (Lander & Poyarekar, 2015) suggest that extraversion may be more closely associated with famous face recognition in particular, but largely support the proposal that extraverts are more effective at face recognition than introverts. In related work, Davis et al (2011) and Megreya & Bindemann (2013) reported that lower levels of social anxiety were associated with better face recognition performance. In the latter study, the authors suggest that the effects of personality on face recognition are limited to traits related to neuroticism, which is contrary to the aforementioned results suggesting that extraversion may also influence face recognition ability.…”
Section: Discussionmentioning
confidence: 97%
“…Yet, there are large individual differences in the ability to recognise (Bowles et al, 2009; Russell, Duchaine & Nakayama, 2009) and perceive (Megreya & Bindemann, 2013; Megreya & Burton, 2006) faces, and particular difficulties are associated with the processing of unfamiliar facial stimuli (see Hancock, Bruce & Burton, 2000 for a review). For instance, over 80 trials, Bruce et al (1999) asked participants to select a face from an array of 10 that matched the identity of a target face.…”
mentioning
confidence: 99%